Conductive paste, cured product, and semiconductor device

By introducing carbon-carbon double bond compounds and thermoplastic resins into the conductive paste to adjust the rheology, the problem of insufficient adhesion of the conductive paste is solved, and the synchronous improvement of the adhesion and thermal conductivity of the conductive paste is achieved, and it is suitable for semiconductor devices.

CN120418940APending Publication Date: 2025-08-01SUMITOMO BAKELITE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380089222.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-28
Filing Date
2023-12-21
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

The existing conductive paste has shortcomings in adhesion, and it is difficult to meet the high adhesion requirements of semiconductor devices.

Method used

The adhesion and thermal conductivity of the conductive paste are improved by adjusting the rheology and curing process using a composition containing a compound having a carbon-carbon double bond, a thermoplastic resin and a conductive particle.

Benefits of technology

The adhesion and thermal conductivity of the conductive paste are synchronously improved, and the reliability and performance of the semiconductor device are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120418940A_ABST
    Figure CN120418940A_ABST
Patent Text Reader

Abstract

A conductive paste containing a compound (A) having a carbon-carbon double bond, a thermoplastic resin (B), and conductive particles (C).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a conductive paste, a cured product, and a semiconductor device. Background Art

[0002] A semiconductor device in which a semiconductor element is fixed using a conductive paste called a chip bonding paste on a substrate such as a lead frame is widely used.

[0003] For example, after fixing a semiconductor element such as an IC or LSI to a lead frame using a chip bonding paste, the lead portion of the lead frame is connected to an electrode on the semiconductor element using a fine wire (bonding wire), and then they are housed in a package to obtain a semiconductor product.

[0004] For the chip bonding paste, adhesion (bonding strength) for fixing the semiconductor element is required. To achieve this, various studies have been made on each component incorporated in the paste.

[0005] For example, in Patent Document 1, a conductive composition is disclosed, which contains: (A) silver fine particles having a number average particle diameter of primary particles of 40 nm to 400 nm; (B) a solvent; and (C) thermoplastic resin particles having a maximum value of an endothermic peak in a DSC curve obtained by measurement using a differential scanning calorimeter in the range of 80°C to 170°C, and it is disclosed that the thermoplastic resin particles in the conductive composition are deformed during sintering of the silver fine particles and follow the shrinkage during curing of the conductive composition, thereby being able to suppress the generation of pores and maintain the bonding strength.

[0006] Prior Art Documents

[0007] Patent Documents

[0008] Patent Document 1: International Publication No. 2016 / 063931 Summary of the Invention

[0009] Technical Problem to be Solved by the Invention

[0010] As described above, for the conductive paste, improvement in adhesion is required.

[0011] The present invention provides a conductive paste with improved adhesion.

[0012] Means for Solving the Technical Problem

[0013] The present inventors have completed the invention provided below and solved the above technical problem. [1]

[0015] A conductive paste, characterized by comprising a compound (A) having a carbon-carbon double bond, a thermoplastic resin (B), and conductive particles (C). [2]

[0017] The electrically conductive paste according to [1] above is characterized in that:

[0018] The thermoplastic resin (B) includes one or more selected from the group consisting of polyester, polyurethane, polyamide, polyimide, polycarbonate, polyolefin, and polyethylene glycol. [3]

[0020] The electrically conductive paste according to [1] or [2] above is characterized in that:

[0021] The thermoplastic resin (B) includes one or more selected from the group consisting of polyamide and polyolefin. [4]

[0023] The electrically conductive paste according to any one of [1] to [3] above is characterized in that:

[0024] The thermoplastic resin (B) includes one or more selected from the group consisting of nylon 12, nylon 11, and nylon 6. [5]

[0026] The electrically conductive paste according to any one of [1] to [4] above is characterized in that:

[0027] The thermoplastic resin (B) includes polyethylene. [6]

[0029] The electrically conductive paste according to any one of [1] to [5] above is characterized in that:

[0030] The melting point of the thermoplastic resin (B) is 80°C or higher and 220°C or lower. [7]

[0032] The electrically conductive paste according to any one of [1] to [6] above is characterized in that:

[0033] The compound (A) includes a (meth)acrylic acid monomer. [8]

[0035] The electrically conductive paste according to any one of [1] to [7] above is characterized in that:

[0036] The compound (A) includes a (meth)acrylic acid monomer having a hydroxyl group. [9]

[0038] The electrically conductive paste according to any one of [1] to [8] above is characterized in that:

[0039] The compound (A) includes a (meth)acrylic acid monomer having an oxyalkylene skeleton.

[10]

[0041] The electrically conductive paste according to any one of [1] to [9] above is characterized in that:

[0042] The compound (A) contains one or more selected from monofunctional (meth)acrylic monomers (A1) and polyfunctional (meth)acrylic monomers (A2).

[11]

[0044] The electrically conductive paste according to any one of [1] to

[10] above is characterized in that:

[0045] The electrically conductive paste further contains an epoxy resin.

[12]

[0047] The electrically conductive paste according to any one of [1] to

[11] above is characterized in that:

[0048] The electrically conductive paste further contains a coupling agent.

[13]

[0050] The electrically conductive paste according to any one of [1] to

[12] above is characterized in that:

[0051] The chip shear strength at 25 °C measured by the following <Method> is 23 N / 2 mm × 2 mm or more,

[0052] <Method>

[0053] The electrically conductive paste is applied to a silver-plated copper substrate so that the cured thickness becomes 20 μm, and a silicon chip with a length of 2 mm × width of 2 mm × height of 0.35 mm coated with gold is mounted, heated from 30 °C to 200 °C in 60 minutes, and heat-treated at 200 °C for 120 minutes to cure the electrically conductive paste to form a cured product, thereby obtaining a test piece for evaluation. Using the obtained test piece for evaluation, the chip shear strength between the silver-plated copper substrate and the cured product is obtained under the conditions of 25 °C and a load speed of 500 μm / second.

[14]

[0055] The electrically conductive paste according to any one of [1] to

[13] above is characterized in that:

[0056] The chip shear strength at 260 °C measured by the following <Method> is 16 N / 2 mm × 2 mm or more,

[0057] <Method>

[0058] The conductive paste was applied to a silver-plated copper substrate such that the thickness after curing was 20 μm, and a silicon chip having a length of 2 mm × width of 2 mm × height of 0.35 mm and coated with gold was mounted thereon. The temperature was raised from 30°C to 200°C over 60 minutes and heat-treated at 200°C for 120 minutes to cure the conductive paste to form a cured product, thereby obtaining a test piece for evaluation. Using the obtained test piece for evaluation, the chip shear strength between the silver-plated copper substrate and the cured product was obtained under the conditions of 260°C and a loading speed of 500 μm / second.

[15]

[0060] The conductive paste according to any one of the above [1] to

[14] , characterized in that:

[0061] The thermal conductivity at 25°C measured by the following <Method> is 30 W / mK or more.

[0062] <Method>

[0063] The conductive paste was applied to a TEFLON (registered trademark) plate, and the temperature was raised from 30°C to 200°C at a constant speed over 60 minutes and then heated at 200°C for 120 minutes to obtain a cured product sample having a length of 10 mm × width of 10 mm × height of 1 mm. The obtained cured product sample was peeled off from the TEFLON (registered trademark) plate, and the thermal conductivity in the thickness direction at 25°C was measured by the laser flash method.

[16]

[0065] The conductive paste according to any one of the above [1] to

[15] , characterized in that:

[0066] The conductive paste is for chip bonding.

[17]

[0068] A cured product which is a cured product of the conductive paste according to any one of the above [1] to

[16] .

[18]

[0070] A semiconductor device, characterized by comprising: a substrate; and a semiconductor element mounted on the substrate via an adhesive layer, wherein the adhesive layer is a cured product of the conductive paste according to any one of the above [1] to

[16] .

[0071] Advantages of the Invention

[0072] According to the present invention, a conductive paste with improved adhesion can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] Figure 1 It is a cross-sectional view showing an example of the semiconductor device of the present embodiment. Detailed Embodiment

[0074] Hereinafter, the present invention will be described according to the embodiments.

[0075] Among the components in the conductive paste in the present embodiment, components such as solvents that volatilize when the conductive paste is cured are referred to as volatile components. On the other hand, components that remain in the cured product when the conductive paste is cured are referred to as non-volatile components. And, components other than the conductive particles (C) in the non-volatile components are referred to as varnish components.

[0076] In the description of the groups (atomic groups) in the present embodiment, there is no description of substitution or non-substitution, including both groups without substituents and groups with substituents. For example, "alkyl" includes not only alkyls without substituents (unsubstituted alkyls) but also alkyls with substituents (substituted alkyls).

[0077] [Conductive Paste]

[0078] The conductive paste of the present embodiment contains a compound (A) having a carbon-carbon double bond, a thermoplastic resin (B), and conductive particles (C).

[0079] According to the present embodiment, a conductive paste with improved adhesion can be provided.

[0080] In the field of conductive pastes, not only is an improvement in adhesion required, but also heat generated within a semiconductor device needs to be released to the outside of the semiconductor device. That is, for a conductive paste, it is required to have good thermal conductivity while improving adhesion. According to the present embodiment, a conductive paste with good thermal conductivity and improved adhesion can also be provided.

[0081] The mechanism by which the conductive paste of the present embodiment has good thermal conductivity and improved adhesion is not clear, but the present inventors speculate as follows.

[0082] First of all, generally speaking, when a conductive paste containing conductive particles is heated, the resin component shrinks while curing, whereby the conductive particles aggregate. In this way, the conductive particles come into contact with each other, and a heat transfer path is formed by the mutually contacting conductive particles. At this time, if the conductive particles do not aggregate properly, a proper heat transfer path cannot be formed, resulting in impaired thermal conductivity. Therefore, it is required to adjust the rheology of the paste so that the conductive particles aggregate properly when the resin component cures.

[0083] Regarding this point, it can be considered that when the conductive paste of the present embodiment is cured, the thermoplastic resin (B) contained in the paste softens by heating, and the rheology of the whole paste is adjusted to a range suitable for forming a thermal movement path for the conductive particles. It is speculated that by doing so, a thermal movement path can be appropriately formed, and good thermal conductivity can be obtained.

[0084] Moreover, the conductive paste of the present embodiment is characterized by containing a compound (A) having a carbon-carbon double bond. It is considered that the compound (A) contributes to the improvement of the flexibility of the cured product formed from the conductive paste, and thus it is speculated that the adhesion to the substrate is improved.

[0085] <Compound (A) having a carbon-carbon double bond>

[0086] The conductive paste of the present embodiment contains a compound (A) having a carbon-carbon double bond. When free radicals are generated in the system, the carbon-carbon double bond of the compound (A) breaks, and the reaction between the compounds (A) or the reaction between the compound (A) and other components proceeds.

[0087] The compound (A) of the present embodiment preferably contains a (meth)acrylic acid monomer. The type of the (meth)acrylic acid monomer is not particularly limited, and as long as it is a (meth)acrylic acid monomer having a (meth)acrylic acid group, it can be used without particular limitation.

[0088] The compound (A) of the present embodiment preferably contains a (meth)acrylic acid monomer having a hydroxyl group.

[0089] The compound (A) of the present embodiment contains a (meth)acrylic acid monomer having an oxyalkylene skeleton.

[0090] (Meth)acrylic acid monomers can be roughly classified into: a monofunctional (meth)acrylic acid monomer (A1) which has only one (meth)acrylic acid group in the molecule; and a polyfunctional (meth)acrylic acid monomer (A2) which has two or more (meth)acrylic acid groups in the molecule.

[0091] From the viewpoints of reducing the viscosity of the paste and imparting flexibility to the cured product of the paste, etc., the compound (A) of the present embodiment preferably contains one or more selected from the monofunctional (meth)acrylic acid monomer (A1) and the polyfunctional (meth)acrylic acid monomer (A2), and more preferably contains the monofunctional (meth)acrylic acid monomer (A1).

[0092] Mono-functional (meth)acrylic monomers (A1) having a hydroxyl group, for example, containing one or more selected from 1,4-cyclohexanedimethanol mono(meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate, preferably containing 1,4-cyclohexanedimethanol mono(meth)acrylate, more preferably containing 1,4-cyclohexanedimethanol monoacrylate.

[0093] Mono-functional (meth)acrylic monomers (A1) having an oxyalkylene skeleton, for example, containing one or more selected from ethoxydiethylene glycol (meth)acrylate, butoxydiethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 2-ethylhexyl diethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxydipropylene glycol (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, nonylphenol ethylene oxide modified (meth)acrylate, phenylphenol ethylene oxide modified (meth)acrylate, polyethylene glycol mono(meth)acrylate, and polypropylene glycol mono(meth)acrylate, preferably containing one or more selected from polyethylene glycol mono(meth)acrylate and polypropylene glycol mono(meth)acrylate, more preferably containing polypropylene glycol mono(meth)acrylate, and further preferably containing polypropylene glycol monomethacrylate.

[0094] Mono-functional (meth)acrylic monomers (A1) not having a hydroxyl group or an oxyalkylene skeleton, for example, containing one or more selected from ethyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, isoamyl acrylate, 2-ethylhexyl methacrylate, isodecyl methacrylate, lauryl acrylate, lauryl methacrylate, n-tridecyl methacrylate, n-stearyl acrylate, n-stearyl methacrylate, isostearyl acrylate, cyclohexyl methacrylate, tetrahydrofurfuryl acrylate, tetrahydrofurfuryl methacrylate, benzyl methacrylate, phenoxyethyl acrylate, phenoxyethyl methacrylate, isobornyl acrylate, isobornyl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, quaternized dimethylaminoethyl methacrylate, glycidyl methacrylate, and neopentyl glycol acrylate benzoate.

[0095] Poly-functional (meth)acrylic monomers (A2) having a hydroxyl group, for example, containing N,N'-(1,2-dihydroxyethylene) bis(meth)acrylamide.

[0096] Poly-functional (meth)acrylic monomers (A2) having an oxyalkylene skeleton, for example, containing triethylene glycol di(meth)acrylate.

[0097] A polyfunctional (meth)acrylic monomer (A2) that does not have a hydroxyl group or an oxyalkylene skeleton, for example, contains one or more selected from 4,4'-isopropylidenediphenol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,6-bis((meth)acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, 1,4-bis((meth)acryloyloxy)butane, 1,6-bis((meth)acryloyloxy)hexane, neopentyl glycol di(meth)acrylate, N,N'-di(meth)acryloylethylenediamine, and 1,4-bis((meth)acryloyl)piperazine.

[0098] When the total amount of the varnish component of the conductive paste of the present embodiment is set to 100 parts by mass, from the viewpoint of adjusting the viscosity of the conductive paste, the content of the compound (A) is preferably 1 part by mass or more, more preferably 5 parts by mass or more, further preferably 10 parts by mass or more, further preferably 15 parts by mass or more, further preferably 19 parts by mass or more, and preferably 90 parts by mass or less, more preferably 70 parts by mass or less, further preferably 50 parts by mass or less, further preferably 40 parts by mass or less, further preferably 30 parts by mass or less, further preferably 21 parts by mass or less.

[0099] <Thermoplastic resin (B)>

[0100] The conductive paste of the present embodiment contains a thermoplastic resin (B). The conductive paste of the present embodiment is characterized by containing a thermoplastic resin (B), and it is presumed that when the conductive paste is cured by heating, the thermoplastic resin (B) softens and contributes to the adjustment of the rheology of the entire conductive paste.

[0101] From the viewpoint of appropriately adjusting the rheology when the conductive paste is cured by heating, the thermoplastic resin (B) of the present embodiment preferably contains one or more selected from polyester, polyurethane, polyamide, polyimide, polycarbonate, polyolefin, and polyethylene glycol.

[0102] From the viewpoint of appropriately adjusting the rheology when the conductive paste is cured by heating, the thermoplastic resin (B) of the present embodiment preferably contains polyamide, more preferably contains nylon, and further preferably contains one or more selected from nylon 12, nylon 11, and nylon 6.

[0103] From the viewpoint of appropriately adjusting the rheology when the conductive paste is cured by heating, the thermoplastic resin (B) of the present embodiment preferably contains polyolefin, and more preferably contains polyethylene.

[0104] From the viewpoint of appropriately adjusting the rheology during heat curing of the conductive paste, the thermoplastic resin (B) in the present embodiment preferably contains one or more selected from polyamides and polyolefins, and more preferably contains one or more selected from polyamides and polyethylene.

[0105] From the viewpoint of appropriately adjusting the rheology during heat curing of the conductive paste, the thermoplastic resin (B) in the present embodiment preferably contains one or more selected from nylons and polyolefins, and more preferably contains one or more selected from nylons and polyethylene.

[0106] From the viewpoint of appropriately adjusting the rheology during heat curing of the conductive paste, the thermoplastic resin (B) in the present embodiment preferably contains one or more selected from nylon 12, nylon 11, nylon 6 and polyolefins, and more preferably contains one or more selected from nylon 12, nylon 11, nylon 6 and polyethylene.

[0107] From the viewpoint of appropriately adjusting the rheology during heat curing of the conductive paste, the melting point of the thermoplastic resin (B) in the present embodiment is preferably 80 °C or higher, more preferably 90 °C or higher, further preferably 100 °C or higher, further preferably 110 °C or higher, further preferably 120 °C or higher, further preferably 130 °C or higher, and preferably 220 °C or lower, more preferably 210 °C or lower, further preferably 200 °C or lower, further preferably 190 °C or lower, further preferably 180 °C or lower, further preferably 170 °C or lower, further preferably 160 °C or lower, further preferably 150 °C or lower, further preferably 140 °C or lower, and preferably 80 °C or higher and 220 °C or lower, more preferably 90 °C or higher and 210 °C or lower, further preferably 100 °C or higher and 200 °C or lower, further preferably 110 °C or higher and 190 °C or lower, further preferably 120 °C or higher and 180 °C or lower, further preferably 130 °C or higher and 170 °C or lower, further preferably 130 °C or higher and 160 °C or lower, further preferably 130 °C or higher and 150 °C or lower, further preferably 130 °C or higher and 140 °C or lower.

[0108] The melting point of the thermoplastic resin (B) in the present embodiment can be measured, for example, by a differential scanning calorimeter (DSC). In the case of measurement by DSC, the maximum value of the endothermic peak in the DSC curve is taken as the melting point.

[0109] From the viewpoint of appropriately adjusting the rheology during heat curing of the conductive paste, the shape of the thermoplastic resin (B) in the present embodiment is preferably granular or fibrous.

[0110] When the shape of the thermoplastic resin (B) in the present embodiment is granular, from the viewpoint of appropriately adjusting the rheology during heat curing of the conductive paste, the particle diameter D at 50% cumulative in the volume-based particle size distribution of the thermoplastic resin (B) 50 is preferably 1 μm or more, more preferably 2 μm or more, still more preferably 5 μm or more, and is preferably 500 μm or less, more preferably 200 μm or less, still more preferably 100 μm or less, still more preferably 50 μm or less, still more preferably 20 μm or less, and is preferably 1 μm or more and 500 μm or less, more preferably 1 μm or more and 200 μm or less, still more preferably 1 μm or more and 100 μm or less, still more preferably 2 μm or more and 50 μm or less, still more preferably 5 μm or more and 20 μm or less.

[0111] When the shape of the thermoplastic resin (B) in the present embodiment is granular, its D 50 can be determined, for example, by the micrograph method or the Coulter counter method for measuring the particle diameter using micrographs. More specifically, the volume-based median particle diameter obtained by these methods can be used as the particle diameter D 50 .

[0112] When the shape of the thermoplastic resin (B) in the present embodiment is fibrous, from the viewpoint of appropriately adjusting the rheology during heat curing of the conductive paste, the average fiber diameter of the thermoplastic resin (B) is preferably 1 μm or more, more preferably 2 μm or more, still more preferably 5 μm or more, and is preferably 100 μm or less, more preferably 50 μm or less, still more preferably 20 μm or less, and is preferably 1 μm or more and 100 μm or less, more preferably 2 μm or more and 50 μm or less, still more preferably 5 μm or more and 20 μm or less.

[0113] And, from the viewpoint of appropriately adjusting the rheology during heat curing of the conductive paste, the average fiber length of the thermoplastic resin (B) is preferably 50 μm or more, more preferably 70 μm or more, still more preferably 100 μm or more, and is preferably 10,000 μm or less, more preferably 5,000 μm or less, still more preferably 2,000 μm or less, still more preferably 1,000 μm or less, still more preferably 500 μm or less, and is preferably 50 μm or more and 10,000 μm or less, more preferably 50 μm or more and 5,000 μm or less, still more preferably 50 μm or more and 2,000 μm or less, still more preferably 70 μm or more and 1,000 μm or less, still more preferably 100 μm or more and 500 μm or less.

[0114] The average fiber diameter and the average fiber length can be measured using a fiber image analyzer such as Valmet FS5 manufactured by Valmet Automation Co., Ltd.

[0115] When the total amount of the varnish components of the conductive paste of the present embodiment is set to 100 parts by mass, from the viewpoint of appropriately adjusting the rheology during heating and curing of the conductive paste, the content of the thermoplastic resin (B) is preferably 1 part by mass or more, more preferably 5 parts by mass or more, further preferably 10 parts by mass or more, further preferably 15 parts by mass or more, further preferably 17 parts by mass or more, and is preferably 90 parts by mass or less, more preferably 70 parts by mass or less, further preferably 50 parts by mass or less, further preferably 40 parts by mass or less, further preferably 30 parts by mass or less, and is preferably 1 part by mass or more and 90 parts by mass or less, more preferably 5 parts by mass or more and 70 parts by mass or less, further preferably 10 parts by mass or more and 50 parts by mass or less, further preferably 15 parts by mass or more and 40 parts by mass or less, further preferably 17 parts by mass or more and 30 parts by mass or less.

[0116] <Conductive particles (C)>

[0117] The conductive paste of the present embodiment contains conductive particles (C). The type of the conductive particles (C) is not particularly limited, and any particles having conductivity can be used without particular limitation.

[0118] The conductive particles (C) are not particularly limited, and examples include: metal particles such as silver particles, gold particles, and copper particles; and metal-coated particles such as silver-coated particles.

[0119] Commercially available products of metal particles such as silver particles can be obtained from, for example, TOKURIKI HONTEN Co., Ltd., Fukuda Metal Foil & Powder Co., Ltd., DOWA HIGHTECH CO., LTD., etc. In addition, commercially available products of metal-coated particles such as silver-coated particles can be obtained from, for example, Mitsubishi Materials Corporation, Sekisui Chemical Co., Ltd., Sanno Co., Ltd., etc.

[0120] The shape of the conductive particles (C) is not particularly limited, and examples include spherical, ellipsoidal, flaky, and scaly shapes.

[0121] From the viewpoint of improving the dispersibility of the conductive particles (C), the shape of the conductive particles (C) is preferably spherical, and from the viewpoint of improving conductivity, the shape of the conductive particles (C) is preferably flaky. Further, from the viewpoint of improving the balance between the conductivity of the adhesive layer and the dispersibility of the conductive particles (C), the conductive particles (C) preferably contain particles having both spherical and flaky shapes.

[0122] The particle size D at 50% cumulative in the volume-based particle size distribution of the conductive particles (C) 50 is preferably 0.3 μm or more, more preferably 0.5 μm or more, still more preferably 0.8 μm or more, and preferably 5 μm or less, more preferably 4.5 μm or less, still more preferably 4 μm or less.

[0123] The D of the conductive particles (C) 50 For example, it can be determined by measuring particle images using a flow particle image analyzer FPIA (registered trademark)-3000 manufactured by Sysmex Corporation. More specifically, the volume-based median particle size obtained using the above device can be used as the particle size D. 50 [[ID=I2]].

[0124] From the viewpoints of improving conductivity and thermal conductivity, when the total amount of the conductive paste is 100 parts by mass, the content of the conductive particles (C) in the conductive paste is preferably 50 parts by mass or more, more preferably 55 parts by mass or more, still more preferably 60 parts by mass or more, still more preferably 70 parts by mass or more, still more preferably 75 parts by mass or more, still more preferably 80 parts by mass or more. Further, from the viewpoint of keeping the viscosity of the conductive paste within an appropriate range, the content of the conductive particles (C) in the conductive paste is preferably 99 parts by mass or less, more preferably 97 parts by mass or less, still more preferably 95 parts by mass or less, still more preferably 93 parts by mass or less, still more preferably 90 parts by mass or less.

[0125] <Other Components>

[0126] The conductive paste of the present embodiment may further contain other components in addition to the above components. Hereinafter, the other components will be described.

[0127] (Epoxy Resin)

[0128] From the viewpoint of appropriately curing the conductive paste, the conductive paste of the present embodiment preferably contains an epoxy resin. The type of the epoxy resin is not particularly limited as long as it is a resin having one or more epoxy groups in the molecule.

[0129] A monofunctional epoxy compound having only one epoxy group in the molecule, for example, containing one or more selected from tert-butylphenyl glycidyl ether, m,p-cresol glycidyl ether, and phenyl glycidyl ether.

[0130] A polyfunctional epoxy compound having two or more epoxy groups in the molecule, for example, containing one or more selected from compounds obtained by epoxidizing bisphenol compounds such as bisphenol A, bisphenol F, and biphenol or their derivatives; compounds obtained by epoxidizing diols having an alicyclic structure such as hydrogenated bisphenol A, hydrogenated bisphenol F, hydrogenated biphenol, cyclohexanediol, cyclohexanedimethanol, and cyclohexanediethanol or their derivatives; compounds obtained by epoxidizing aliphatic diols such as butanediol, hexanediol, octanediol, nonanediol, and decanediol or their derivatives; compounds obtained by epoxidizing compounds having a trimethylolpropane skeleton, a trihydroxyphenylmethane skeleton, or an aminophenol skeleton or their derivatives; and compounds obtained by epoxidizing phenol novolac resin, cresol novolac resin, phenol aralkyl resin, biphenyl aralkyl resin, naphthol aralkyl resin, or their derivatives, preferably containing one or more selected from compounds obtained by epoxidizing compounds having a trimethylolpropane skeleton, a trihydroxyphenylmethane skeleton, or an aminophenol skeleton or their derivatives, more preferably containing one or more selected from compounds obtained by epoxidizing derivatives of compounds having a trimethylolpropane skeleton, and further preferably containing trimethylolpropane polyglycidyl ether.

[0131] When the conductive paste of the present embodiment contains an epoxy resin, from the viewpoint of appropriately curing the conductive paste, when the total amount of the varnish components of the conductive paste of the present embodiment is set to 100 parts by mass, the content of the epoxy resin is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, further preferably 20 parts by mass or more, further preferably 30 parts by mass or more, further preferably 40 parts by mass or more, and preferably 90 parts by mass or less, more preferably 80 parts by mass or less, further preferably 70 parts by mass or less, and further preferably 60 parts by mass or less.

[0132] (Curing agent)

[0133] The conductive paste of the present embodiment may contain a curing agent. The type of the curing agent is not particularly limited as long as it is a substance capable of reacting with the epoxy resin to cure it.

[0134] The curing agent of this embodiment includes, for example, phenol novolac-type phenolic resins selected from phenol novolac resins, cresol novolac resins, bisphenol novolac resins, phenol-biphenyl novolac resins, etc.; polyvinylphenol; multifunctional phenolic resins such as triphenylmethane-type phenolic resins; modified phenolic resins such as terpene-modified phenolic resins and dicyclopentadiene-modified phenolic resins; phenol aralkyl-type phenolic resins such as phenol aralkyl resins having a phenylene skeleton and / or a biphenylene skeleton, and naphthol aralkyl resins having a phenylene and / or a biphenylene skeleton; bisphenol compounds such as bisphenol A and bisphenol F (dihydroxydiphenylmethane); and one or more of compounds having a biphenylene skeleton such as biphenol, preferably including one or more of bisphenol compounds such as bisphenol A and bisphenol F (dihydroxydiphenylmethane), and more preferably including bisphenol F (dihydroxydiphenylmethane).

[0135] In the case where the conductive paste of the present embodiment contains a curing agent, from the viewpoint of properly curing the conductive paste, the content of the curing agent when the total amount of the varnish component of the conductive paste of the present embodiment is set to 100 parts by mass is preferably 1 part by mass or more, more preferably 5 parts by mass or more, further preferably 10 parts by mass or more, further preferably 15 parts by mass or more, and preferably 90 parts by mass or less, more preferably 70 parts by mass or less, further preferably 50 parts by mass or less, further preferably 40 parts by mass or less, further preferably 30 parts by mass or less.

[0136] (Curing aid)

[0137] The conductive paste of this embodiment may contain a curing aid. The type of the curing aid is not particularly limited, as long as it can promote the reaction between the epoxy resin and the curing agent.

[0138] The curing aid of this embodiment includes, for example, 2-phenylimidazole, 2-phenyl-1H-imidazole-4,5-dimethanol, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-methylimidazole, 2,4-diamino-6-[2-methylimidazolyl-(1)]-ethyl-s-triazine, 2-undecylimidazole, 2-heptadecylimidazole, 2,4-diamino-6-[2-methylimidazolyl-(1)]-ethyl-s-triazine triisocyanate adduct, 2-phenylimidazole ... -phenylimidazole isocyanurate adduct, 2-methylimidazole isocyanurate adduct, 1-cyanoethyl-2-phenylimidazolium tricarboxylate and 1-cyanoethyl-2-undecylimidazolium tricarboxylate, preferably contains one or more selected from 2-phenylimidazole, 2-phenyl-1H-imidazole-4,5-dimethanol, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, more preferably contains 2-phenyl-4,5-dihydroxymethylimidazole.

[0139] When the conductive paste of the present embodiment contains a curing aid, from the viewpoint of appropriately curing the conductive paste, when the total amount of the varnish component of the conductive paste of the present embodiment is set to 100 parts by mass, the content of the curing aid is preferably 0.01 part by mass or more, more preferably 0.1 part by mass or more, further preferably 0.5 part by mass or more, further preferably 1.0 part by mass or more, further preferably 1.2 part by mass or more, and preferably 20 parts by mass or less, more preferably 10 parts by mass or less, further preferably 5 parts by mass or less, further preferably 2 parts by mass or less.

[0140] (Free radical polymerization initiator)

[0141] The conductive paste of the present embodiment may contain a free radical polymerization initiator. The type of the free radical polymerization initiator is not particularly limited as long as it is a polymerization initiator capable of generating free radicals in the system.

[0142] The free radical polymerization initiator of the present embodiment includes, for example, one or more selected from ketone peroxides such as methyl ethyl ketone peroxide and cyclohexanone peroxide; peroxyketals such as 1,1-bis(tert-butylperoxy)cyclohexane and 2,2-bis(4,4-bis(tert-butylperoxy)cyclohexyl)propane; hydroperoxides such as p-menthane hydroperoxide, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, cumene hydroperoxide, and tert-butyl hydroperoxide; dialkyl peroxides such as bis(1-phenyl-1-methylethyl)peroxide, di(2-tert-butylperoxyisopropyl)benzene, di-α-isopropylbenzyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, tert-butylisopropylbenzyl peroxide, di-tert-hexyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexyne-3, and di-tert-butyl peroxide; diacyl peroxides such as dibenzoyl peroxide and di(4-methylbenzoyl)peroxide; peroxydicarbonates such as di-n-propyl peroxydicarbonate and diisopropyl peroxydicarbonate; and peroxyesters such as 2,5-dimethyl-2,5-bis(benzoylperoxy)hexane, tert-hexyl peroxybenzoate, tert-butyl peroxybenzoate, and tert-butyl peroxy-2-ethylhexanoate. Preferably, it includes one or more selected from dialkyl peroxides such as bis(1-phenyl-1-methylethyl)peroxide, di(2-tert-butylperoxyisopropyl)benzene, di-α-isopropylbenzyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, tert-butylisopropylbenzyl peroxide, di-tert-hexyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexyne-3, and di-tert-butyl peroxide. More preferably, it includes di-α-isopropylbenzyl peroxide.

[0143] When the conductive paste of the present embodiment contains a radical polymerization initiator, the content of the radical polymerization initiator is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, further preferably 0.5 parts by mass or more, still further preferably 1.0 parts by mass or more, and preferably 20 parts by mass or less, more preferably 10 parts by mass or less, further preferably 5 parts by mass or less, still further preferably 2 parts by mass or less, still further preferably 1.5 parts by mass or less, based on 100 parts by mass of the total amount of the varnish component of the conductive paste of the present embodiment.

[0144] (Coupling agent)

[0145] From the viewpoint of improving the adhesion to the substrate, the conductive paste of the present embodiment preferably contains a coupling agent.

[0146] The coupling agent is not particularly limited. For example, it includes one or more selected from vinyl silanes such as vinyltrimethoxysilane and vinyltriethoxysilane; epoxy silanes such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxypropyltriethoxysilane; styryl silanes such as p-styryltrimethoxysilane; methacryloyl silanes such as 3-methacryloyloxypropylmethyldimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropylmethyldiethoxysilane, and 3-methacryloyloxypropyltriethoxysilane; (meth)acrylic acid silanes such as 3-(trimethoxysilyl)propyl methacrylate and 3-acryloyloxypropyltrimethoxysilane; amino silanes such as N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, and trimethoxy[3-(phenylamino)propyl]silane; polyisocyanate silane; alkyl silane; ureido silanes such as 3-ureidopropyltrialkoxysilane; mercapto silanes such as 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, and bis[3-(triethoxysilyl)propyl]polysulfide; and isocyanate silanes such as 3-isocyanatopropyltriethoxysilane. Preferably, it includes one or more selected from epoxy silanes such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxypropyltriethoxysilane; styryl silanes such as p-styryltrimethoxysilane; and methacryloyl silanes such as 3-methacryloyloxypropylmethyldimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropylmethyldiethoxysilane, and 3-methacryloyloxypropyltriethoxysilane. More preferably, it includes one or two selected from 3-glycidoxypropyltrimethoxysilane and 3-methacryloyloxypropyltrimethoxysilane.

[0147] When the conductive paste of the present embodiment contains a coupling agent, when the total amount of the varnish component of the conductive paste of the present embodiment is set to 100 parts by mass, the content of the coupling agent is preferably 0.01 part by mass or more, more preferably 0.1 part by mass or more, further preferably 0.5 part by mass or more, further preferably 1.0 part by mass or more, further preferably 1.5 part by mass or more, and preferably 20 parts by mass or less, more preferably 10 parts by mass or less, further preferably 5 parts by mass or less, further preferably 3 parts by mass or less.

[0148] (Solvent)

[0149] The conductive paste of the present embodiment may contain a solvent. The type of the solvent is not particularly limited as long as it is a solvent that can volatilize when the conductive paste is cured.

[0150] The solvent is not particularly limited. For example, it includes one or more of alcohols such as ethanol, propanol, butanol, pentanol, hexanol, heptanol, octanol, nonanol, decanol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, methyl methoxybutanol, α-terpineol, β-terpineol, hexylene glycol, benzyl alcohol, 2-phenylethanol, isopalmitol, isostearyl alcohol, lauryl alcohol, ethylene glycol, propylene glycol or glycerol; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, diacetone alcohol (4-hydroxy-4-methyl-2-pentanone), 2-octanone, isophorone (3,5,5-trimethyl-2-cyclohexen-1-one) or diisobutyl ketone (2,6-dimethyl-4-heptanone); esters such as ethyl acetate, butyl acetate, diethyl phthalate, dibutyl phthalate, acetoxyethane, methyl butyrate, methyl caproate, methyl caprylate, methyl caprate, methyl cellosolve acetate, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, 1,2-diacetoxyethane, tributyl phosphate, tricresyl phosphate or tripentyl phosphate; ethers such as tetrahydrofuran, dipropyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, propylene glycol dimethyl ether, ethoxyethyl ether, 1,2-bis(2-diethoxy)ethane or 1,2-bis(2-methoxyethoxy)ethane, ethylene glycol mono-2-ethylhexyl ether, tripropylene glycol monon-butyl ether; ester ethers such as 2-(2-butoxyethoxy)ethyl acetate; ether alcohols such as 2-(2-methoxyethoxy)ethanol; hydrocarbons such as toluene, xylene, n-alkanes, isoparaffins, dodecylbenzene, turpentine, kerosene or light oil; nitriles such as acetonitrile or propionitrile; amides such as acetamide or N,N-dimethylformamide; silicone oils such as low molecular weight volatile silicone oils and volatile organically modified silicone oils. More preferably, it includes one or more of ethers such as tetrahydrofuran, dipropyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, propylene glycol dimethyl ether, ethoxyethyl ether, 1,2-bis(2-diethoxy)ethane or 1,2-bis(2-methoxyethoxy)ethane, ethylene glycol mono-2-ethylhexyl ether, tripropylene glycol monon-butyl ether. Even more preferably, it includes one or two of ethylene glycol mono-2-ethylhexyl ether and tripropylene glycol monon-butyl ether.

[0151] When the conductive paste in the present embodiment contains a solvent, the content of the solvent in the conductive paste can be arbitrarily set according to the viscosity to be set. From the viewpoint of adjusting the viscosity of the conductive paste, for example, it is 1 part by mass or more, for example, 2 parts by mass or more, for example, 5 parts by mass or more, and, for example, 90 parts by mass or less, for example, 70 parts by mass or less, for example, 50 parts by mass or less.

[0152] As other components contained in the conductive paste, known components such as a filler, a polymerization inhibitor, an antifoaming agent, a surfactant, a colorant, etc. can be used in addition. The content of these other components can be arbitrarily set according to the physical properties desired to be imparted to the conductive paste.

[0153] The conductive paste of the present embodiment can be manufactured by mixing the above-described respective components by a conventionally known method.

[0154] <Properties of the Conductive Paste>

[0155] The conductive paste of the present embodiment preferably has a die shear strength at 25°C measured by the following <Method> of 23 N / 2 mm × 2 mm or more, more preferably 30 N / 2 mm × 2 mm or more, further preferably 40 N / 2 mm × 2 mm or more, further preferably 50 N / 2 mm × 2 mm or more, further preferably 54 N / 2 mm × 2 mm or more, further preferably 65 N / 2 mm × 2 mm or more, further preferably 90 N / 2 mm × 2 mm or more, further preferably 100 N / 2 mm × 2 mm or more, further preferably 104 N / 2 mm × 2 mm or more, and, for example, 500 N / 2 mm × 2 mm or less, for example, 400 N / 2 mm × 2 mm or less, for example, 300 N / 2 mm × 2 mm or less, for example, 200 N / 2 mm × 2 mm or less, for example, 150 N / 2 mm × 2 mm or less.

[0156] <Method>

[0157] The conductive paste is applied onto a silver-plated copper substrate so that the thickness after curing becomes 20 μm, and a silicon chip having a length of 2 mm × a width of 2 mm × a height of 0.35 mm coated with gold is mounted. It is heated from 30°C to 200°C over 60 minutes and heat-treated at 200°C for 120 minutes to cure the conductive paste to form a cured product, thereby obtaining a test piece for evaluation. Using the obtained test piece for evaluation, the die shear strength between the silver-plated copper substrate and the cured product is obtained under the conditions of 25°C and a load speed of 500 μm / second.

[0158] The conductive paste of the present embodiment preferably has a die shear strength at 260 °C measured by the following <Method> of 16 N / 2 mm×2 mm or more, more preferably 20 N / 2 mm×2 mm or more, further preferably 24 N / 2 mm×2 mm or more, further preferably 28 N / 2 mm×2 mm or more, further preferably 32 N / 2 mm×2 mm or more, further preferably 40 N / 2 mm×2 mm or more, further preferably 44 N / 2 mm×2 mm or more, and, for example, 200 N / 2 mm×2 mm or less, for example, 100 N / 2 mm×2 mm or less, for example, 70 N / 2 mm×2 mm or less.

[0159] <Method>

[0160] The conductive paste is applied to a silver-plated copper substrate so that the cured thickness becomes 20 μm, and a silicon chip having a length of 2 mm×width of 2 mm×height of 0.35 mm coated with gold is mounted. It is heated from 30 °C to 200 °C over 60 minutes and heat-treated at 200 °C for 120 minutes to cure the conductive paste to form a cured product, thereby obtaining a test piece for evaluation. Using the obtained test piece for evaluation, the die shear strength between the silver-plated copper substrate and the cured product is obtained under the conditions of 260 °C and a load speed of 500 μm / second.

[0161] The conductive paste of the present embodiment preferably has a die shear strength at 25 °C measured by the following <Method> of 20 N / 2 mm×2 mm or more, more preferably 25 N / 2 mm×2 mm or more, further preferably 27 N / 2 mm×2 mm or more, further preferably 30 N / 2 mm×2 mm or more, further preferably 35 N / 2 mm×2 mm or more, and, for example, 200 N / 2 mm×2 mm or less, for example, 100 N / 2 mm×2 mm or less, for example, 50 N / 2 mm×2 mm or less.

[0162] <Method>

[0163] The conductive paste is applied to a copper substrate so that the cured thickness becomes 20 μm, and a silicon chip having a length of 2 mm×width of 2 mm×height of 0.35 mm is mounted. It is heated from 30 °C to 200 °C over 60 minutes and heat-treated at 200 °C for 120 minutes to cure the conductive paste to form a cured product, thereby obtaining a test piece for evaluation. Using the obtained test piece for evaluation, the die shear strength between the copper substrate and the cured product is obtained under the conditions of 25 °C and a load speed of 500 μm / second.

[0164] The conductive paste of the present embodiment preferably has a chip shear strength at 260°C measured by the following <Method> of 10 N / 2 mm×2 mm or more, more preferably 12 N / 2 mm×2 mm or more, still more preferably 15 N / 2 mm×2 mm or more, and, for example, 100 N / 2 mm×2 mm or less, for example, 50 N / 2 mm×2 mm or less, for example, 25 N / 2 mm×2 mm or less.

[0165] <Method>

[0166] The conductive paste is applied to a copper substrate so that the cured thickness becomes 20 μm, and a silicon chip having a length of 2 mm×width of 2 mm×height of 0.35 mm is mounted. It is heated from 30°C to 200°C over 60 minutes and heat-treated at 200°C for 120 minutes to cure the conductive paste to form a cured product, thereby obtaining a test piece for evaluation. Using the obtained test piece for evaluation, the chip shear strength between the copper substrate and the cured product is obtained under the conditions of 260°C and a load speed of 500 μm / second.

[0167] The conductive paste of the present embodiment has a dynamic storage modulus (dynamic storage elastic modulus) at 25°C measured by the following <Method> of, for example, 1 GPa or more, for example, 2 GPa or more, for example, 4 GPa or more, for example, 6 GPa or more, for example, 6.3 GPa or more, and is preferably 50 GPa or less, more preferably 30 GPa or less, still more preferably 20 GPa or less, still more preferably 16 GPa or less, still more preferably 12 GPa or less, still more preferably 10 GPa or less, still more preferably 9 GPa or less, still more preferably 7 GPa or less.

[0168] <Method>

[0169] The conductive paste is applied to a TEFLON (registered trademark) plate and heated from 30°C to 200°C at a constant speed over 60 minutes, and then continuously heated at 200°C for 120 minutes to obtain a cured product sample having a length of 20 mm×width of 4 mm×height of 0.3 mm. The obtained cured product sample is peeled off from the TEFLON (registered trademark) plate, and the dynamic storage modulus is measured at 25°C, in a tensile mode, and at a frequency of 10 Hz.

[0170] The dynamic storage modulus at 250 °C of the conductive paste of the present embodiment, measured by the following <Method>, is, for example, 0.1 GPa or more, for example, 0.5 GPa or more, for example, 1.0 GPa or more, and is preferably 20 GPa or less, more preferably 10 GPa or less, further preferably 6 GPa or less, further preferably 4.5 GPa or less, further preferably 3.5 GPa or less, further preferably 2.5 GPa or less, further preferably 1.5 GPa or less.

[0171] <Method>

[0172] Apply the conductive paste onto a TEFLON (registered trademark) plate, heat it from 30 °C to 200 °C at a constant rate over 60 minutes, and continue heating at 200 °C for 120 minutes to obtain a cured product sample with a length of 20 mm × width of 4 mm × height of 0.3 mm. Peel the obtained cured product sample from the TEFLON (registered trademark) plate and measure the dynamic storage modulus at 250 °C under the conditions of tensile mode and a frequency of 10 Hz.

[0173] The thermal conductivity at 25 °C of the conductive paste of the present embodiment, measured by the following <Method>, is preferably 30 W / mK or more, more preferably 40 W / mK or more, further preferably 45 W / mK or more, further preferably 50 W / mK or more, further preferably 55 W / mK or more, further preferably 60 W / mK or more, and is, for example, 500 W / mK or less, for example, 200 W / mK or less, for example, 100 W / mK or less.

[0174] <Method>

[0175] Apply the conductive paste onto a TEFLON (registered trademark) plate, heat it from 30 °C to 200 °C at a constant rate over 60 minutes, and continue heating at 200 °C for 120 minutes to obtain a cured product sample with a length of 10 mm × width of 10 mm × height of 1 mm. Peel the obtained cured product sample from the TEFLON (registered trademark) plate and measure the thermal conductivity in the thickness direction at 25 °C by the laser flash method.

[0176] The use of the conductive paste of the present embodiment is not particularly limited, but since the conductive paste of the present embodiment has good thermal conductivity and improved adhesion, it is preferably used as a die bonding application for bonding semiconductor elements onto a support such as a substrate in a semiconductor device.

[0177] [Cured product]

[0178] The cured product of the present embodiment is the cured product of the above-mentioned conductive paste.

[0179] The method for curing to obtain the cured product of the present embodiment is not particularly limited. For example, it can be obtained by curing the components in the conductive paste by heat treatment.

[0180] The heat treatment temperature of the conductive paste is preferably 150 °C or higher, more preferably 175 °C or higher, still more preferably 200 °C or higher, and preferably 500 °C or lower, more preferably 400 °C or lower, still more preferably 300 °C or lower.

[0181] [Semiconductor device]

[0182] The semiconductor device of the present embodiment includes: a substrate; and a semiconductor element mounted on the substrate via an adhesive layer, wherein the adhesive layer is a cured product of the above-mentioned conductive paste.

[0183] Use Figure 1 An example of the semiconductor device of the present embodiment will be described.

[0184] Figure 1 FIG. is a cross-sectional view showing the semiconductor device 100 of the present embodiment. The semiconductor device 100 of the present embodiment includes: a substrate 30; and a semiconductor element 20 mounted on the substrate 30 via an adhesive layer 10, wherein the adhesive layer 10 is a cured product of the conductive paste.

[0185] The semiconductor element 20 and the substrate 30 are electrically connected via, for example, a bonding wire 40 or the like. And the semiconductor element 20 is sealed by a sealing resin 50, for example.

[0186] The film thickness of the adhesive layer 10 is not particularly limited. For example, it is 5 μm or more, for example, 10 μm or more, for example, 20 μm or more, and, for example, 100 μm or less, for example, 70 μm or less.

[0187] In Figure 1 In the example shown, the substrate 30 is a lead frame composed of a chip pad 32 and an external lead 34. In this case, the semiconductor element 20 is mounted on the chip pad 32 via the chip bonding layer 10. And the semiconductor element 20 is electrically connected to the external lead 34 via the bonding wire 40, for example. The substrate 30 as the lead frame is composed of, for example, a 42 alloy, a Cu frame.

[0188] The substrate 30 can also be an organic substrate or a ceramic substrate. As the organic substrate, a substrate well-known to those skilled in the art using, for example, epoxy resin, cyanate resin, maleimide resin, etc. is preferred. And, in order to have good adhesiveness with the chip bonding paste, the surface of the substrate 30 can be covered with silver or the like.

[0189] The planar shape of the semiconductor element 20 is not particularly limited and is, for example, rectangular. In the present embodiment, a rectangular semiconductor element 20 having a chip size of 0.5 mm × 0.5 mm or more and 15 mm × 15 mm or less can be used, for example.

[0190] The semiconductor device 100 can be manufactured, for example, by the following process.

[0191] First, the above-described conductive paste is applied to the chip pad 32 (substrate 30), and the semiconductor element 20 is mounted on the applied conductive paste. The method of applying the conductive paste is not particularly limited, and examples thereof include a dispensing method, a printing method, and an inkjet method.

[0192] Then, the conductive paste is heat-treated to cure the conductive paste. Thereby, the adhesive layer 10 is formed on the chip pad 32 (substrate 30). The temperature conditions for the heat treatment can be appropriately set according to the composition of the conductive paste and the like.

[0193] Then, the semiconductor element 20 is electrically connected to the external lead 34 (substrate 30) using the bonding wire 40, and the semiconductor element 20 is sealed with the sealing resin 50, whereby the semiconductor device 100 can be obtained.

[0194] The embodiments of the present invention have been described above, but these are examples of the present invention, and various configurations other than the above can also be adopted.

[0195] Examples

[0196] Hereinafter, the present invention will be described by way of examples and comparative examples, but the present invention is not limited thereto.

[0197] [Preparation of Conductive Paste]

[0198] The conductive paste is prepared by uniformly mixing the respective components according to the formulation shown in Table 1. The unit of the content of each component in Table 1 is parts by mass.

[0199] The details of the components shown in Table 1 are as follows.

[0200] Compound (A)

[0201] · (Meth) acrylic monomer 1 (Compound name: 1,4-cyclohexanedimethanol monoacrylate, Product name: CHDMMA, Supplier: Mitsubishi Chemical Corporation)

[0202] · (Meth)acrylic acid monomer 2 (Compound name: Polypropylene glycol monomethacrylate, Product name: BLEMMER PP-800, Provider: NOF CORPORATION)

[0203] Thermoplastic resin (B)

[0204] · Thermoplastic resin 1 (Material: Nylon 12, Melting point: 165°C, D 50 : 5μm, Product name: Toray Nylon Particles SP-500, Provider: TORAY INDUSTRIES, INC.)

[0205] · Thermoplastic resin 2 (Material: Polyethylene, Melting point: 136°C, D 50 : 10μm, Product name: Micro Particles MIPELON PM-200, Provider: MITSUI FINE CHEMICALS, INC.)

[0206] · Thermoplastic resin 3 (Material: Polyolefin, Melting point: 135°C, Fiber length: 100μm, Fiber diameter: 10μm, Product name: KEMIBESTO FDSS-5, Provider: MITSUI FINE CHEMICALS, INC.)

[0207] Conductive particles (C)

[0208] · Silver particles 1 (D 50 : 0.7μm, Product name: AG-DSB-114, Provider: DOWAHIGHTECH CO., LTD.)

[0209] · Silver particles 2 (D 50 : 7.6μm, Product name: HKD-12, Provider: Fukuda Metal Foil & Powder Co., Ltd.)

[0210] · Silver-coated particles 1 (D 50 : 10μm, Provider: Mitsubishi Materials Corporation)

[0211] Other components

[0212] · Epoxy resin 1 (Compound name: Trimethylolpropane polyglycidyl ether, Provider: Nagase ChemteX Corporation)

[0213] · Curing agent 1 (Compound name: Bisphenol F, Supplier: DIC Corporation)

[0214] · Curing aid 1 (Compound name: 2-Phenyl-4,5-dihydroxymethylimidazole, Product name: 2PHZ-PW, Supplier: SHIKOKU KASEI HOLDINGS CORPORATION)

[0215] · Free radical polymerization initiator 1 (Compound name: Di-α-cumyl peroxide, Product name: Perkadox BC, Supplier: Kayaku Akzo Corporation)

[0216] · Coupling agent 1 (Compound name: 3-Methacryloxypropyltrimethoxysilane, Product name: KBM-503P, Supplier: Shin-Etsu Chemical Co., Ltd.)

[0217] · Coupling agent 2 (Compound name: 3-Glycidoxypropyltrimethoxysilane, Product name: KBM-403E, Supplier: Shin-Etsu Chemical Co., Ltd.)

[0218] · Solvent 1 (Compound name: Tripropylene glycol monobutyl ether, Supplier: NIPPONNYUKAZAI CO., LTD.)

[0219] · Solvent 2 (Compound name: Ethylene glycol mono-2-ethylhexyl ether, Product name: 2-Ethylhexanediol, Supplier: NIPPON NYUKAZAI CO., LTD.)

[0220] [Thermal conductivity]

[0221] The conductive paste obtained by the above method was coated on a TEFLON (registered trademark) plate, heated from 30 °C to 200 °C at a certain speed over 60 minutes, and then continuously heated at 200 °C for 120 minutes to obtain a cured sample with a length of 10 mm × width of 10 mm × height of 1 mm. The cured sample obtained was peeled off from the TEFLON (registered trademark) plate, and the thermal conductivity in the thickness direction at 25 °C was measured by the laser flash method. The results are shown in Table 1.

[0222] [Chip shear strength]

[0223] <Silver-plated substrate / gold-coated chip>

[0224] The conductive paste obtained by the above method was applied to a silver-plated copper substrate in such a manner that the thickness after curing became 20 μm, and a silicon chip having a length of 2 mm × width of 2 mm × height of 0.35 mm coated with gold was mounted. It was heated from 30 °C to 200 °C over 60 minutes and heat-treated at 200 °C for 120 minutes to cure the conductive paste to form a cured product, thereby obtaining a test piece for evaluation. Using the obtained test piece for evaluation, the chip shear strength between the silver-plated copper substrate and the cured product was obtained under the conditions of 25 °C and 260 °C and a loading speed of 500 μm / second. The results are shown in Table 1.

[0225] <Copper substrate / Silicon chip>

[0226] The conductive paste obtained by the above method was applied to a copper substrate in such a manner that the thickness after curing became 20 μm, and a silicon chip having a length of 2 mm × width of 2 mm × height of 0.35 mm was mounted. It was heated from 30 °C to 200 °C over 60 minutes and heat-treated at 200 °C for 120 minutes to cure the conductive paste to form a cured product, thereby obtaining a test piece for evaluation. Using the obtained test piece for evaluation, the chip shear strength between the copper substrate and the cured product was obtained under the conditions of 25 °C and 260 °C and a loading speed of 500 μm / second. The results are shown in Table 1.

[0227] [Elastic modulus]

[0228] The conductive paste obtained by the above method was applied to a TEFLON (registered trademark) plate, heated from 30 °C to 200 °C at a constant speed over 60 minutes, and further heated at 200 °C for 120 minutes to obtain a cured product sample having a length of 20 mm × width of 4 mm × height of 0.3 mm. The obtained cured product sample was peeled off from the TEFLON (registered trademark) plate, and the dynamic storage modulus was measured under the conditions of 25 °C and 250 °C, tensile mode, and a frequency of 10 Hz. The results are shown in Table 1.

[0229] [MSL]

[0230] The conductive paste obtained by the above method was applied to the surface of a copper frame in such a manner that the thickness after curing became 20 μm, and a silicon chip having a length of 5 mm × width of 5 mm × height of 0.2 mm was mounted on the applied conductive paste. Then, in an oven under a nitrogen atmosphere, it was heated from 30 °C to 200 °C at a rate of 2.83 °C / minute, and then heat-treated at 200 °C for 120 minutes to obtain a test piece for evaluation.

[0231] The obtained test piece for evaluation was sealed with an epoxy-based encapsulant and heat-treated in an oven at 175 °C for 4 hours for post mold cure to obtain a packaged structure having a length of 14 mm, a width of 14 mm, and a thickness of 0.8 mm.

[0232] The encapsulated structure obtained by the above method is placed in a thermostatic and humidistatic chamber set at a temperature of 60°C and a relative humidity of 60% for 40 hours, and then passed through a reflow oven at 260°C three times at a speed of 67 cm / minute to obtain an encapsulated structure that has completed the MSL (Moisture Sensitivity Level) test.

[0233] Observe the peeling state of the encapsulated structure that has completed the heat test obtained by the above method, and evaluate it according to the following evaluation criteria. The results are shown in Table 1.

[0234] OK: There is no peeling between the conductive paste layer and the copper frame.

[0235] NG: There is peeling between the conductive paste layer and the copper frame.

[0236] [Table 1]

[0237]

[0238]

[0239] As shown in Table 1, in the examples, the chip shear strength is improved. It can be seen from this that by using the conductive paste of the present embodiment, the adhesion can be improved.

[0240] Moreover, as shown in Table 1, in the examples, while maintaining a good value of the thermal conductivity, the chip shear strength is improved. It can be seen from this that by using the conductive paste of the present embodiment, the adhesion can be improved while maintaining good thermal conductivity.

[0241] This application claims priority based on Japanese Patent Application No. 2022-211780 filed on December 28, 2022, and incorporates the entire contents disclosed therein.

[0242] Explanation of Reference Numerals

[0243] 10 Adhesive layer, 20 Semiconductor element, 30 Substrate, 32 Chip pad, 34 Outer lead, 40 Bonding wire, 50 Sealing resin, 100 Semiconductor device.

Claims

1. A conductive paste, characterized in that: It contains a compound (A) having a carbon-carbon double bond, a thermoplastic resin (B), and conductive particles (C).

2. The conductive paste according to claim 1, characterized in that: The thermoplastic resin (B) contains one or more selected from polyester, polyurethane, polyamide, polyimide, polycarbonate, polyolefin, and polyethylene glycol.

3. The conductive paste according to claim 1 or 2, characterized in that: The thermoplastic resin (B) contains one or more selected from polyamide and polyolefin.

4. The conductive paste according to any one of claims 1 to 3, characterized in that: The thermoplastic resin (B) contains one or more selected from nylon 12, nylon 11, and nylon 6.

5. The conductive paste according to any one of claims 1 to 4, characterized in that: The thermoplastic resin (B) contains polyethylene.

6. The conductive paste according to any one of claims 1 to 5, characterized in that: The melting point of the thermoplastic resin (B) is 80 °C or higher and 220 °C or lower.

7. The conductive paste according to any one of claims 1 to 6, characterized in that: The compound (A) contains a (meth)acrylic monomer.

8. The conductive paste according to any one of claims 1 to 7, characterized in that: The compound (A) contains a (meth)acrylic monomer having a hydroxyl group.

9. The conductive paste according to any one of claims 1 to 8, characterized in that: The compound (A) contains a (meth)acrylic monomer having an oxyalkylene skeleton.

10. The conductive paste according to any one of claims 1 to 9, characterized in that: The compound (A) contains one or more selected from monofunctional (meth)acrylic monomers (A1) and polyfunctional (meth)acrylic monomers (A2).

11. The conductive paste according to any one of claims 1 to 10, characterized in that: The conductive paste further contains an epoxy resin.

12. The conductive paste according to any one of claims 1 to 11, characterized in that: The conductive paste further contains a coupling agent.

13. The conductive paste according to any one of claims 1 to 12, characterized in that: The chip shear strength at 25 °C measured by the following <Method> is 23 N / 2 mm × 2 mm or more, <Method> The conductive paste is applied to a silver-plated copper substrate so that the cured thickness becomes 20 μm, and a silicon wafer with a length of 2 mm × width of 2 mm × height of 0.35 mm coated with gold is mounted, heated from 30 °C to 200 °C in 60 minutes, and heat-treated at 200 °C for 120 minutes to cure the conductive paste to form a cured product, thereby obtaining a test piece for evaluation. Using the obtained test piece for evaluation, the chip shear strength between the silver-plated copper substrate and the cured product is obtained under the conditions of 25 °C and a load speed of 500 μm / second.

14. The conductive paste according to any one of claims 1 to 13, characterized in that: The die shear strength at 260 °C measured by the following <Method> is 16 N / 2 mm×2 mm or more. <Method> Apply the conductive paste onto a silver-plated copper substrate such that the thickness after curing is 20 μm, and mount a silicon chip coated with gold having a length of 2 mm×width of 2 mm×height of 0.35 mm. Heat from 30 °C to 200 °C over 60 minutes, and heat-treat at 200 °C for 120 minutes to cure the conductive paste to form a cured product, thereby obtaining a test piece for evaluation. Using the obtained test piece for evaluation, obtain the die shear strength between the silver-plated copper substrate and the cured product under the conditions of 260 °C and a loading rate of 500 μm / second.

15. The conductive paste according to any one of claims 1 to 14, characterized in that: The thermal conductivity at 25 °C measured by the following <Method> is 30 W / mK or more. <Method> Apply the conductive paste onto a TEFLON (registered trademark) plate, heat from 30 °C to 200 °C at a constant rate over 60 minutes, continue to heat at 200 °C for 120 minutes to obtain a cured product sample having a length of 10 mm×width of 10 mm×height of 1 mm. Peel the obtained cured product sample from the TEFLON (registered trademark) plate, and measure the thermal conductivity in the thickness direction at 25 °C by the laser flash method.

16. The conductive paste according to any one of claims 1 to 15, characterized in that: The conductive paste is for die bonding.

17. A cured product which is a cured product of the conductive paste according to any one of claims 1 to 16.

18. A semiconductor device, characterized in that, Comprising: A substrate; And a semiconductor element mounted on the substrate via an adhesive layer, wherein the adhesive layer is a cured product of the conductive paste according to any one of claims 1 to 16.

Citation Information

Patent Citations

  • Conductive composition and electronic component using same

    WO2016063931A1